Classroom Behavior of English Majors at Ho Chi Minh University of Banking in Chinese Language - Vu, Luu Hon (VNU Journal of Science: Education Research; Vol 38 No 2, 2022)
This study investigated the classroom behavior of Chinese as a second foreign language among 246 English majors at Ho Chi Minh City University of Banking. The survey results show that students’ learning orientation has the highest frequency of use, and their dominating others has the lowest frequency of use. In terms of gender, there were significant differences in the frequency of dominating others use between male and female students. In terms of grades, there was a significant difference in the frequency of verbal participation between second- and third-grade students. In terms of home life area, there were no significant differences in various classroom behaviors between students from urban areas and those from rural areas. Students’ academic performance was positively correlated with verbal participation, learning orientation, and support-seeking. Based on the above research results, this study puts forward some teaching suggestions.